2017
DOI: 10.1039/c7ta03824k
|View full text |Cite
|
Sign up to set email alerts
|

An in situ grown bacterial nanocellulose/graphene oxide composite for flexible supercapacitors

Abstract: A flexible supercapacitor electrode with excellent electrochemical performance and mechanical flexibility is fabricated via in situ incorporation of graphene oxide flakes and conducting polymer (PEDOT:PSS) into a layered bacterial nanocellulose network during its growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…On the other hand, because of the layered structure and excellent electrons transport ability after combining with conductive substrates, MoSe 2 and its related hybrids with low volume density and high surface permeability can offer oversized reaction sites and show a negligible change of volume when a facile insertion/extraction process of ions and electrons occurs . These characteristics would result in supramaximal effective specific surface areas and ultrashort electron transfer distance which are critical factors for supercapacitor materials . In general, with more exposed edges of the active sites, larger effective surface areas and better electrons transport ability compared to other TMDs, MoSe 2 with conductive substrates would be potential not only for effective HER catalysts but also for high‐performance supercapacitor electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because of the layered structure and excellent electrons transport ability after combining with conductive substrates, MoSe 2 and its related hybrids with low volume density and high surface permeability can offer oversized reaction sites and show a negligible change of volume when a facile insertion/extraction process of ions and electrons occurs . These characteristics would result in supramaximal effective specific surface areas and ultrashort electron transfer distance which are critical factors for supercapacitor materials . In general, with more exposed edges of the active sites, larger effective surface areas and better electrons transport ability compared to other TMDs, MoSe 2 with conductive substrates would be potential not only for effective HER catalysts but also for high‐performance supercapacitor electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…The composite was stable in water and could selectively separate organic and inorganic ions due to the size of the porosity and the charge of the graphene oxide. More recently it has been demonstrated that a graphene/BNC composite can be directly produced by culturing the bacteria (Gluconacetobacter hansenii) with graphene flakes273 . This method produced highly entangled BNC and graphene with excellent mechanical properties, electrochemical properties and cycling stability.Graphene oxide-cellulose composites have been made as sensitive and selective solvent sensors, based on detecting a change in capacitance upon sorption274 .…”
mentioning
confidence: 99%
“…However, a review by Stoller and Ruoff suggested that the three-electrode configuration is valuable for the determination of electrochemical-specific material characteristics, while a two-electrode configuration portrays the physical configuration, charge transfer, and internal voltage of packaged SCs, thus providing better information on the electrode materials [ 89 ]. Jiang et al reported the in situ incorporation of GO flakes and PEDOT: PSS into the bacterial nanocellulose (BNC) matrix and their electrode materials exhibited a specific capacitance of 373 F/g at a current density of 1 A/g [ 90 ]. Layered double hydroxides (LDHs) have recently been intensely studied as a candidate for SC applications.…”
Section: Advanced Electrodes For Scs: Present Status and Prospectsmentioning
confidence: 99%